Community housing with a focus on spatial progression in the Sergio Toral 1 Cooperative, Guayaquil - Salvador, Andrea; Zambrano, Christian; Saavedra, Lileana (Artes: Architecture, Technology and Sustainability, 2022)
The access to decent and affordable housing in Guayaquil and at the national level is a latent need in terms of aspirations to improve the quality of life of families. Currently, 40% of the population cannot access decent housing, which is why family nuclei choose to settle irregularly in unplanned territories unsuitable for habitation. By this premise, a detailed diagnosis of the site will be prepared around perceived problems such as overcrowding, insecurity, and urban slums. The study’s objective is to develop a housing plan scheme using two models of progressive community housing. First, an iterative analysis methodology with a qualitative-quantitative approach is used to analyze and parameterize the conditions of community housing focused on the progression of its spaces to obtain new schemes for housing plans that are accessible to low-income communities. Within the quantitative method, sequential and rational mathematical analysis is used to evaluate fundamental aspects of design. In conclusion, it is obtained that through the urban iterative process, planned spatial progressions can be obtained and that they improve the functional quality of the integral space and that the mathematical models generate acceptable spectra in the choice of the fundamental aspects.